Immigration, Transition into Adult Life and Social Adversity in Relation to Psychological Distress and Suicide Attempts among Young Adults - Kosidou, Kyriaki (Public Library of Science, 2012)
BACKGROUND: The increasing incidence of mental health problems among young people is a major concern in many Western countries. The causal mechanisms underlying these trends are not well established, but factors influenced by current societal changes ought to be implicated. Such factors include immigration and social adversity as well as the timing of taking on adult social roles (e.g. gainful employment, parenthood and own housing tenure). We therefore examined relationships between these factors and the risks of psychological distress as well as suicide attempts in young adults, with a focus on gender differences. METHODS: We conducted a population-based study including 10,081 individuals aged 18–29, recruited in 2002 and 2006 in Stockholm, Sweden. Data were collected by record linkage and questionnaires. RESULTS: Non-European immigrants had an increased risk of distress, and female non-European immigrants had a markedly higher risk of suicide attempts. Both early parenthood (≤24 years) and not being a parent, being a student and the lack of own housing tenure were associated with distress, but only in women. In both sexes, financial strain was associated with the increased risk of distress and suicide attempts, while unemployment was only associated with distress. CONCLUSIONS: Immigration from outside Europe and social adversity are associated with mental health problems in young adults, especially females. Postponed transition into adulthood is associated with poor mental health in young women. These factors are influenced by current societal changes, and may have contributed to the increasing incidence of mental health problems among young people in Western countries.